Review Article: The Potential of Terpenoids from Marine Organisms as Neuroprotective Agents in Peripheral Neuropathy - Shafira Adinda Putri; Baiq Rizqika Catur Putri; Mulayanatul Aliyyah; Fito Danang Sofiandi; Ilsa Hunaifi (Faculty of Medicine, Universitas Mataram, 2026)
Peripheral neuropathy is a common neurological disorder, particularly in patients with diabetes mellitus and older adults, with limitations of current therapies prompting the search for alternative treatments. This narrative review aims to evaluate the potential of marine-derived terpenoids as neuroprotective agents in peripheral neuropathy. Terpenoids demonstrate multi-target mechanisms, including antioxidant and anti-inflammatory effects, ion channel modulation, and regulation of signaling pathways such as phosphoinositide 3-kinase/protein kinase B (PI3K/Akt), Mitogen Activated Protein Kinase (MAPK), and nuclear factor erythroid 2 related factor 2 (Nrf2). These actions contribute to reduced oxidative stress, suppression of neuroinflammation, and improved neuronal survival. Compounds such as astaxanthin show promising effects in reducing neuropathic pain, although evidence remains largely preclinical. Clinical translation is limited by low bioavailability and insufficient long term safety data. Further studies are required to confirm their therapeutic potential.